2015
DOI: 10.1038/modpathol.2015.43
|View full text |Cite
|
Sign up to set email alerts
|

Refining prognosis and identifying targetable pathways for high-risk endometrial cancer; a TransPORTEC initiative

Abstract: This study aimed to investigate whether molecular analysis can be used to refine risk assessment, direct adjuvant therapy, and identify actionable alterations in high-risk endometrial cancer. TransPORTEC, an international consortium related to the PORTEC3 trial, was established for translational research in high-risk endometrial cancer. In this explorative study, routine molecular analyses were used to detect prognostic subgroups: p53 immunohistochemistry, microsatellite instability and POLE proofreading mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
396
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 389 publications
(428 citation statements)
references
References 35 publications
27
396
0
5
Order By: Relevance
“…The survival advantage of POLE-mutated high-grade endometrioid carcinomas has been observed in multiple studies (10)(11)(12)29) but not all (24). We did not show a significant association between grade, histology, and POLE status; however, we did confirm that POLE-mutated grade 3 endometrial carcinomas have an excellent prognosis.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The survival advantage of POLE-mutated high-grade endometrioid carcinomas has been observed in multiple studies (10)(11)(12)29) but not all (24). We did not show a significant association between grade, histology, and POLE status; however, we did confirm that POLE-mutated grade 3 endometrial carcinomas have an excellent prognosis.…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies have demonstrated that POLE-mutated cases are mostly grade 3 endometrial carcinomas (11,12,29). To compare with these studies, we also assessed the outcome of all POLE-mutated grade 3 tumor histologies.…”
Section: Clinical Outcome Of Pole-mutated Endometrial Carcinomasmentioning
confidence: 99%
“…Evaluations were done independently with discrepancies resolved at simultaneous viewing. For DNA analyses, tumor DNA was isolated as reported previously (11).…”
Section: Methodsmentioning
confidence: 99%
“…Integrated genomic characterization by The Cancer Genome Atlas (TCGA) defined four distinct endometrial carcinoma subgroups with possible prognostic value (10). Using methods broadly available in clinical practice, these four subgroups can be easily determined by their surrogate markers: p53, microsatellite instability (MSI), and POLE resulting in a practically and clinically useful molecular classification tool (11,12). In relatively small series of unselected endometrial carcinomas, the combination of both the clinicopathologic and molecular classification improved the clinicopathologic risk assessment (12).…”
Section: Introductionmentioning
confidence: 99%
“…The TCGA prognostic classification has been recently validated in 152 endometrial carcinoma cases. 62,63 Utility of immunohistochemical and molecular tools in distinguishing SC from EEC Histological type has consistently been proved to be an important predictor of survival, but also a determinant for the extent of the initial surgical procedure and subsequent use of adjuvant therapy. There is moderate to excellent agreement (0.62-0.87) in overall histologic typing, but also significant interobserver variability among high-grade tumors.…”
Section: Molecular Features Of Scmentioning
confidence: 99%